PENGARUH LATIHAN SEATED TRICEPS EXTENSION TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA TIM VOLLY PUTRA SMP NEGERI 3 TELUK KUANTAN - Putra Damai; Ramadi, S.Pd, M.Kes '; Kristi Agust, S.Pd, M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract. The problem in this research is the ability to smash in volleyball men's SMP Negeri 3 Teluk Kuantan, allegedly because of the low strength of arm muscles. The purpose of this study was to know the effect of exercise ntuk Seated Triceps Extension on the arm and shoulder muscle strength in men's volleyball team at SMP Negeri 3 Teluk Kuantan. This type of research and engineering experimental research sample full (total sampling) with a sample size of 11 people. Data were collected through tests of muscle strength of arms and shoulders by using test Pull-Up. Data analysis using t test data normality test with lilifors techniques. Based on preliminary tests, the results of data analysis L0 max = 0.0345 with 0.05 L α table, then L0 max <Ltabel, 0.0345 <0.249. While the final test results obtained L0 max = 0.0578 with 0.05 L α table. Then L0 max <Ltabel, 0.0578 <0.249 with 10 df, and test hypotheses obtained t = 2.91, while table = 1,812. The conclusion of this study is there Effect Against exercise Seated Triceps Extension Arm and Shoulder Muscle Strength By Tim Volly Putra SMP Negeri 3 Teluk Kuantan.Key Words: Triceps Extension Seated Exercise and Muscle Strength Arm and Shoulder